Genetic Analysis of Variability and Divergence in French Bean (Phaseolus vulgaris L.) - Panda, A.; Paul, A.; Mohapatra, P. (International Journal of Bio-resource and Stress Management, 2023)
Field experiments were conducted during two consecutive rabi seasons i.e. 2011–12 and 2012–13 in four locations of district Nayagarh in Odisha to evaluate 28 genotypes of French bean for 13 morphological traits. The per se performance of genotypes showed that HAFB-1 ranked first for 6 out of 13 characters. Combined analysis of GCV, heritability and genetic advance showed that the traits such as plant height, number of pods plant-1 and number of secondary branches plant-1 would respond effectively for phenotypic selection. The D2 analysis grouped the genotypes into 7 clusters, out of which 2 were mono-genotypic cluster. There was grouping of genotypes of diverse origin into single cluster. The inter-cluster distance values were more than intra-cluster values suggesting more heterogeneity among clusters. Clusters VII, V, IV, VI were found to be highly divergent than rest of the clusters. So crosses among the clusters may be taken for producing superior genotypes. The cluster-IV showed high mean values for pod yield, single pod weight, number of podsplant-1, green pod breadth, number of primary and secondary branches plant-1, whereas Cluster-V recorded high green pod length and plant height. So the genotypes from both the cluster may be crossed to incorporate desirable traits. Plant height contributed maximum towards divergence. Cluster analysis on the basis of D2 was correlated with canonical analysis. Pooled analysis of variability and divergence showed that the genotypes HAFB-1, HAFB-5, HAFB-6, PDR-14, IIHR-4 may be included in hybridization programme for producing superior genotypes and wide segregants in fillial generations.